Clinical Studies Using Biological and Synthetic Materials for Meniscus Replacement - D Lin, David; E. Picardo, Natasha; Adesida, Adetola; S Khan, Wasim (Current Stem Cell Research & Therapy, 2017)
Meniscal injury is a common problem among sportsmen and increasingly seen in the older and more active population. The traditional treatment options include a partial meniscectomy, which provides good mechanical and pain relief to the patient. However, the focus of treatment is shifting towards repairing meniscal tears where possible and replacement of the lost meniscal tissue where appropriate. Replacement can be total or partial. Total meniscal replacement using an allograft, is usually reserved for young patients, who meet certain criteria and who have undergone several subtotal meniscectomies or a single stage total meniscectomy and are still symptomatic. Partial meniscal replacement can be utilized in conjunction with a partial meniscectomy to fill the resulting space left by the resection. Collagen based implants and synthetic scaffolds have entered the European market but have demonstrated mixed results in clinical trials. Tissue engineering to create an implant that mimics the biomechanical properties holds much potential for future research.
Keywords: meniscectomy